Chromosomes of the marine prawn Parapenaeopsis stylifera - ., Mukesh; Sharma, K; Lakra, W S (Indian Journal of Fisheries, 2011)
A chromosomal study was conducted on a marine prawn, Parapenaoepsis stylifera. The metaphase spreads were prepared from the hepatopancreatic tissue. The species possessed a modal diploid number (2n) of 74 chromosomes, FN = 110. The karyotype comprised of 1 metacentric, 18 submetacentric, 1 subtelocentric and 17 acrocentric pairs. The size of the chromosome ranged from 1.89 to 9.84 pm. Sex chromosomes were cytologically indistinguishable.